Depression exacerbates AD pathology through lactate-dependent activation of microglial Kv1.3 to promote Aβ-containing exosome spreading - Xiaoli Liu; Huijin Wang; Xi Tian; Yingqi Luo; Minmin Ma; Zilong Zheng; Yaping Wang; Shi Feng; Qiushi Wang; Zhuo Xu; Wen Yao; Siqiang Ren (Journal of Neuroinflammation)
Abstract Depression has been widely recognized as an important accelerating factor contributing to the aggravation of cognitive decline in Alzheimer’s disease (AD) patients. Previous studies show that microglia-mediated neuroinflammation is a common and critical event in the etiology of both depression and dementia, but whether and how microglia participate in the process of depression-exacerbating AD pathology is largely unknown. By establishing the learned helplessness depression model on 5×FAD mice, we confirmed that depression can indeed promote Aβ plaque deposition and deteriorate the cognitive performance of the AD mice. Importantly, we found that microglial lactate concentration is dramatically increased in the depressed AD brain, leading to activation of potassium channel Kv1.3 likely through non-direct-lactylation. The activated Kv1.3 further facilitates Aβ-containing exosome spreading from microglia in the vicinity of Aβ plaque into the surrounding brain tissue. Notably, conditional knock-out of Kv1.3 in microglia can reverse the depression-induced acceleration of AD pathology and cognitive decline. Together, our study highlights an important function of microglia Kv1.3 in the promotion of Aβ propagation in the context of depression-exacerbating AD pathology.